Late Cenozoic deformation of the Da'an-Dedu Fault Zone and its implications for the earthquake activities in the Songliao basin, NE China. (1st August 2015) - Zhongyuan, Yu; Peizhen, Zhang; Wei, Min; Qinghai, Wei; Limei, Wang; Bin, Zhao; Shuang, Liu; Jian, Kang
Highlights: The DDFZ formed inverted faults in the 3rd evolutionary stages of the Songliao Basin. The kinetic features of the DDFZ in Quaternary show as strike-slip and thrust-folds. Modern earthquakes in the Songliao Basin were controlled by the deformation of the DDFZ. We report moderate earthquake potential and seismic hazards along the DDFZ in the future. Contraction tectonic deformation has dominated NE China since ∼65 Ma. Abstract: The Da'an-Dedu Fault Zone is a major tectonic feature cutting through the Songliao Basin from south to north in NE China. Five earthquakes with magnitudes over 5 that occurred during the past 30 years suggest the fault zone is a seismogenic structure with future seismic potential. The structural pattern, tectonic history, Quaternary activity and seismic potential have previously been unknown due to the Quaternary sedimentary coverage and lack of large historic earthquakes ( M > 7). In this paper, we use seismic reflection profiles and drilling from petroleum explorations and shallow-depth seismic reflections to study those problems. The total length of the Da'an-Dedu Fault Zone is more than 400 km; modern seismicity delineates it into 4 segments each with a length of 90–100 km. In cross-section view, the folds and associated faults form a complex structural belt with a width of more than 10 km. Shallow-level seismic reflection across the Da'an-Dedu Fault Zone reveals that the Late Quaternary sediments were folded and faulted, indicating its present tectonic activity. The Da'an-Dedu Fault Zone and Songliao Basin have been subjected to three stages of tectonic evolution: a rifting stage characterized by normal faulting and extension (∼145–112 Ma), a prolonged stage of thermal subsidence (∼112–65 Ma), and a tectonic reversal that has been taking place since ∼65 Ma. Our shallow-level reflection profiles show that the folding and reverse faulting have influenced the Late Quaternary sediments. The seismicity and moderate earthquakes suggest that the tectonic activity persists today. The deformation rate across the Da'an-Dedu Fault Zone, however, is measured to be very slow. In conjunction with the inference that most deformation in NE China may be taken up by the Yilan-Yitong Fault Zone bounding the Songliao Basin to the east, we suggest moderate earthquake potential and thus moderate seismic hazards along the Da'an-Dedu Fault Zone. The geological structures, which include anticlines and reverse faults, imply that the Da'an-Dedu Fault Zone has been a contractive structure since ∼65 Ma, and this type of contraction dominates the tectonic deformation in the Songliao Basin and the entire NE China, although the reasons for these conditions need to be further studied.